Corporate governance practices and corporate social responsibility of financial institutions in sri lanka - Jeyan Suganya, D.F.; Kengatharan, L.; Pinthuja, V. (University of Jaffna, 2021)
Financial institutions play a major role in the economy and society to provide better financial services to the people in a country. This study aims to examine to what extent corporate governance practices impact on corporate social responsibility of financial institutions in Sri Lanka. For the purpose of analysis 12 banks, 17 finance companies and 7 insurance companies listed in Colombo Stock Exchange were selected based on the availability of data, which was collected for the period of five years from 2014 to 2018. Board size, women directors on board, audit committee and independent directors on board were considered as independent variables and firm size and return on assets were used as control variable. Corporate Social Responsibility Disclosures was considered as dependent variable. The major statistical method used in the study was Pooled Ordinary Least Square regression analysis. The results of the study demonstrate that, corporate governance proxy as women directors on board has positive significant impact on corporate social responsibility. In addition the control variable namely firm size statistically significant with corporate social responsibility. Further, shows that Board size, Audit committee, independent directors on board and Return on Assets don't have significant impact on corporate social responsibility. Overall study implies that gender diversity actually has an impact on corporate social responsibility of the firm. Therefore, financial firms in Sri Lanka can increase number of women on board as they are considered as socially responsible for sustainable practices.
Keywords: Corporate social responsibility; corporate governance; Financial institutions